(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Post-war existentialist poetry is characterized by resorting to a symbolic heritage of myths and signs from the Holy Scriptures, as well as using the verse from the wisdom books of the Bible as a favorite metrical resource. Banished like the Edenic couple or the angel Lucifer, the poets find themselves figuratively and literally in an adverse and unrecognizable reality –Spain after the establishment of Francoism–, crying out to a deity that seems alien to human evil and distant. The idiosyncrasy of this style is not a rhetorical peculiarity typical of the 40s, but rather it is attached to a previous lyrical tradition that comes from the mysticism of the 16th century, but which is rooted in a certain 1990s spirituality, reaching its climax with Rosario de sonetos líricos (1912) and El Cristo de Velázquez (1920), by Miguel de Unamuno. The present work intends to trace the biblical and Unamuno traces in the main existentialist poetizations, analyzing the relationship of continuity and rupture that postwar poets establish with their primary sources, on the one hand; on the other, to demonstrate the subversive role played by biblical language, since, by virtue of its universal value, it manages to name contemporary nonconformity and unease.